BREAKING THE CYCLE: RETHINKING VIOLENCE AGAINST WOMEN AND PATHWAYS TO JUSTICE IN INDIA - Dr. Shabir Ahmad Lone; Dr. Kulatunga Mudiyanselage Rohitha Dasanayaka; Dr. R. Abida Begum; Dr. Alemayehu Erkihun Engida (RADJA PUBLIKA, 2026)
This research paper examines the ongoing problem of violence against women in India by exploring its different forms and social consequences. It discusses the difficulty of clearly defining such violence and the challenges this creates for research due to the sensitive nature of the issue. The study explains how factors such as patriarchy, unequal power relations, and social norms contribute to sexual violence. Although laws and programs exist, violence often remains underreported. The study stresses the need for stronger laws and better research to address the problem effectively.